2018
DOI: 10.21475/ajcs.18.12.03.pne801
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ACC deaminase producing Pseudomonas fluorescens strains for their effects on seed germination and early growth of wheat under salt stress

Abstract: Plant growth-promoting rhizobacteria possessing ACC deaminase activity reduces the level of stress ethylene, conferring resistance and improving plant growth under different stress conditions. The present study aims at evaluating Pseudomonas fluorescens strains for their potential to produce ACC deaminase and quantifying their effects on seed germination and seedling growth of wheat under salinity stress. Bacteria were first evaluated for their ability to utilize ACC, an immediate precursor of stress ethylene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 27 publications
1
8
0
4
Order By: Relevance
“…The ethylene is a significant plant hormone required for every aspect of plant development and growth cycle but it stimulates, growth repressive effects, such as retardation of root development, inhibition of seed germination, promotion of aging, senescence and abscission process in plants under stressed conditions (Gupta and Pandey, 2019). Several reports suggested that application of ACC deaminase producers mitigate the adverse effect of salt stress manifested on plants by minimizing the ethylene emission to its optimum level and thus confers growth promotion and stress tolerance in stressed plants (Orhan, 2016; Maxton et al, 2018; Safari et al, 2018). The growth of French bean plants when subjected to salinity stress might be attributed to the ACC deaminase activity (>20 nmol α-ketobutyrate mg protein -1 h -1 ) of two selected strains, which declines the production of stress generated ethylene by deaminating its precursors, ACC into ammonia and α-ketobutyrate (Penrose and Glick, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The ethylene is a significant plant hormone required for every aspect of plant development and growth cycle but it stimulates, growth repressive effects, such as retardation of root development, inhibition of seed germination, promotion of aging, senescence and abscission process in plants under stressed conditions (Gupta and Pandey, 2019). Several reports suggested that application of ACC deaminase producers mitigate the adverse effect of salt stress manifested on plants by minimizing the ethylene emission to its optimum level and thus confers growth promotion and stress tolerance in stressed plants (Orhan, 2016; Maxton et al, 2018; Safari et al, 2018). The growth of French bean plants when subjected to salinity stress might be attributed to the ACC deaminase activity (>20 nmol α-ketobutyrate mg protein -1 h -1 ) of two selected strains, which declines the production of stress generated ethylene by deaminating its precursors, ACC into ammonia and α-ketobutyrate (Penrose and Glick, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of a homolog of AtERF38 (GhERF38 from G. hirsutum) in Arabidopsis resulted in ABA sensitivity in transgenic lines; therefore, reduced seed germination under salinity and drought stress was observed in the transgenic plants as compared to WT [101]. Plant growth-promoting Pseudomonas fluorescens strains improve salinity tolerance of plants due to its ability to produce ACC deaminase and, consequently, to stimulate seed germination in wheat under salinity stress [102]. With the higher activity of ACC deaminase, the Enterobacter cloacae HSNJ4 strain could effectively promote seed germination and could provide the salinity tolerance by degrading ACC, thus inhibiting ethylene synthesis [103].…”
Section: Seed Germination Regulated By Ethylene Under Salinity Stressmentioning
confidence: 99%
“…Pseudomonas fluorescens, Enterobacter hormaechei, and Pseudomonas migulae are three ACC and EPS producing microbes which when inoculated in foxtail millet could promote seedling germination in drought condition 75 . PGPR possessing ACC deaminase activity reduce toxicity of heavy metals, drought stress and other abiotic stresses like extreme temperature, salinity and soil pH, besides, antagonism against phytopathogens 76 73 . Leclercia adecarboxylata and Agrobacterium fabrum, Bacillus amyloliquifaciens with higher ACC-deaminase and IAA production traits elevated nutrients uptake and high chlorophyll contents 78,79 .…”
Section: Acc Deaminase Production By Rhizobacteriamentioning
confidence: 99%